Labor Force Status Dynamics in the German Labor Market: Individual Heterogeneity and Cyclical Sensitivity - Jochen Kluve; Sandra Schaffner; Christoph M. Schmidt (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2006)
The aggregate average unemployment rate in a given country is essentially the result of individual workers' transitions between the three core labor force states, employment, unemployment, and inactivity. The dynamics of these transitions depend both on individual duration in a particular state and the transition probabilities between states. Individual transitions, in turn, depend on personal characteristics, i.e. observable sociodemographic attributes and unobserved factors. Simultaneously, person-specific dynamics may be influenced by swings of the business cycle that differentially affect the likelihood of individual transitions. This paper analyzes these labor force status dynamics for the German labor market using comprehensive data on monthly transitions from the GSOEP, covering the time periods 1983-2003 for West Germany, and 1992-2003 for East Germany. For 18 demographic cells defined by sex, 3 age categories, and 3 education categories, the model uses loading factors to translate unobserved shocks to the labor market into observed cellspecific unemployment rates as well as bilateral transition probabilities between all states. This approach allows us to distinguish individual heterogeneity and cyclical volatility in describing labor force status flows. The results show that the experience of high unemployment rates is more sensitive to cyclical behavior for certain demographic groups, specifically unskilled and young workers. Heterogeneity in unemployment and transition rates differs between East and West Germany, as well as between the sexes. In East Germany, all demographic cells are almost entirely detached from the cycle. The unemployment structure of West German women is rather homogenous across age and education, in contrast to men and East-German women. The decisive component of the heterogeneity in unemployment dynamics is the re-employment rate.
Keywords: J64; J21; E32; 519; Labor force; Unemployment dynamics; Business Cycle; Worker heterogeneity